TRANSFORMASI ASESMEN DI SMA: MEMPERKUAT LITERASI SAINS DAN LINGKUNGAN UNTUK SISWA KELAS X - Jeramat, Eufrasia; Ningsi, Gabariela Purnama; Raga, Polikarpus; Kurnila, Valeria Suryani (Universitas Lancang Kuning, 2024)
school students related to increasing awareness and concern for science and the environment in Ecosystem Materials. This type of research is research and development with a 4-D development model. Research subjects consisted of 40 class X students and validators consisted of 3 lecturers and 1 teacher. The research instruments used were validation sheets. Research data types are qualitative and quantitative data. The research shows that the scientific literacy-based assessment instrument is very valid logically with a percentage of 95.52% and the environmental literacy-based instrument with a percentage of 90.64% is very valid. Empirically, with a range of 0.35-0.75 for multiple choice questions, a range of 0.42-0.80 for essays. The results of the practicality assessment by teachers for instruments based on scientific literacy were 95.16% and environmental literacy was 96%. Meanwhile, instruments based on scientific literacy by students are 95.5% and environmental literacy is 94.25%. High reliability results with a range of 0.75% for multiple choice questions and description questions with very high reliability with a range of 0.88% Based on the research results, it can be concluded that the assessment instruments based on scientific literacy and environmental literacy on Ecosystem X material can be said to be suitable for use in the learning process. Suggestions that can be made are that teachers can develop assessment instruments in other materials to be able to optimize learning and develop innovative assessments that can increase students' understanding, motivate them to take action, and lead to a more caring attitude towards science and the environment. The implication of this research is the importance of a holistic, student-centered assessment approach in educating a generation that has high awareness and concern for science and environmental issues.